Las remesas y su incidencia en el nivel de producción a corto plazo - Roca Garay, Richard (2009)
The article discusses the potential impact of remittances on the level of domestic output under fixed exchange rate and flexible with high capital mobility and finds that it would have an expansionary effect if the exchange rate and contractive if the exchange rate is free.